2020
DOI: 10.1186/s40623-020-1144-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of plastic strain using GNSS data of pre- and post-seismic deformation of the 2011 Tohoku-oki earthquake

Abstract: In general, there are three mechanisms causing crustal deformation: elastic, viscous, and plastic deformation. The separation of observed crustal deformation to each component has been a challenging problem. In this study, we succeed in separating plastic deformation as well as viscous deformation in the northern Niigata–Kobe Tectonic Zone (NKTZ), central Japan, using GNSS data before and after the 2011 Tohoku-oki earthquake, under the assumptions that elastic deformation is principally caused by the plate cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The estimated loading rates of this region are a several times larger than those obtained from the GPS data in the plane strain framework. However, our finding that the pre-M9 term rate is the double of the post-M9 term well agrees with that obtained for EW-deformation rate in Niigata (Fukahata et al, 2020). For a long-term hazard estimation of the eastern margin of the Japan Sea area, the rates we obtained will be another proxy values.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The estimated loading rates of this region are a several times larger than those obtained from the GPS data in the plane strain framework. However, our finding that the pre-M9 term rate is the double of the post-M9 term well agrees with that obtained for EW-deformation rate in Niigata (Fukahata et al, 2020). For a long-term hazard estimation of the eastern margin of the Japan Sea area, the rates we obtained will be another proxy values.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of horizontal strain obtained from GPS data for the eastern margin of the Japan Sea before the M9 event (Sagiya, 2004) is a quarter of what we obtained in this study. Fukahata et al (2020) obtained EW-direction deformation rates from GPS data in the Niigata region as 6×10 -8 /y for pre-M9, and 3×10 -8 /y for post-M9 terms. Their strain rates are two dimensional.…”
Section: Discussionmentioning
confidence: 99%
“…For example, applying the method to GNSS data in Japan, Sagiya et al (2000) found a high strain-rate region named the Niigata-Kobe tectonic zone (NKTZ) that passes through central Japan. Furthermore, through the analysis of GNSS data in this region before and after the 2011 Tohoku-oki earthquake, Meneses-Gutierrez and Sagiya (2016) succeeded in separating elastic strain and inelastic strain; Fukahata et al (2020) further succeeded in separating the inelastic strain into plastic and viscous strains. Nishimura et al (2018) clarified strain partitioning between inland active faults and the interplate coupling in southwest Japan.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the strain-rate eld, we use the surface displacement data of GEONET, a GNSS array by the Geospatial Information Authority of Japan (GSI), as in many previous studies (e.g., Sagiya et al 2000;Nishimura et al 2018;Fukahata et al 2020). In recent years, several methods have been developed for calculating strain rates from surface displacement data that can take into account the spatial heterogeneity of station spacing (Shen et al 2015;Sandwell and Wessel 2016;Okazaki et al 2021).…”
Section: Introductionmentioning
confidence: 99%